Design of a digital tunable stellar spectrum calibration source based on a digital micromirror device. (15th March 2022) - Xu, Da; Sun, Gaofei; Zhang, Guoyu; Zhang, Yu; Wang, Li; Liu, Shi; Zhong, Jun; Liang, Shitong; Yang, Junjie
Highlights: A spectral tunable radiometric calibration source with dual operating modes (monochromatic light and wide spectrum) is proposed. The cylindrical collimating beam expanding system is used to reduce the aperture of the spectral modulation system, and improves the spectral modulation accuracy and spectral resolution. The simulation accuracy (point by point scanning) of target spectrum is between 2.8% and 5.1% in broad-band mode. The output monochromatic full width at half maximum (FWHM) is between 2.75 nm and 3.86 nm in narrow-band mode. Abstract: A design method of spectral tunable radiation source with supercontinuum laser as the radiation source and digital micro-mirror device (DMD) as the spectral modulation device is proposed. Adopt the design idea of reducing the relative aperture of the spectral imaging system to improve the imaging quality, use cylindrical collimating beam expanding system to replace the collimating objective in the traditional spectral imaging system, and the relative aperture of the system is reduced in the dispersion direction. According to the test results, in narrow-band mode, the maximum full width at half maximum (FWHM) of monochromatic light bandwidth in the spectrum range of 450–1000 nm is 3.86 nm. In the broad-band mode, four typical stellar color temperature of T = 2600 K, 3500 K, 7000 K, 11, 000 K are simulated, and the simulation results show that the accuracy of the star spectrum is better than 3.1% at 2600 K, 4.2% at 3500 K, 2.8% at 7000 K and 5.1% at 11, 000 K.